2011
DOI: 10.21608/eajbsa.2011.15171
|View full text |Cite
|
Sign up to set email alerts
|

Role of pteromalid parasitoid Scutellista caerulea (Fonscolombe) (Hymenoptera: Pteromalidae) for biological control of the soft scale insects (Hemiptera: Coccidae) in Egypt

Abstract: The pteromalid parasitoid, Scutellista caerulea (Fonscolombe) (Hymenoptera: Pteromalidae) is one of the most effective parasitoid associated with soft scale insects. This work dealt with the biological role of this parasitoid during 2009 and 2010 in Egypt. The results indicated that the parasitoid, S. caerulea was emerged from 8 species of soft scale insects. The host soft scale insects were Ceroplastes floridensis Comstock, Ceroplastes rusci (L.), Coccus hesperidum L., Kilifia acuminata (Signoret), Parasaisse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Ben-Dov and Guerrieri (2009) recorded the parasitoid Anicetus africanus (Girault) (Hymenoptera, Encyrtidae) newly recorded from Israel associated with W. mimosae. Badary and Abd-Rabou (2011) mentioned that the pteromalid parasitoid, Scutellista caerulea (Fonscolombe) (Hymenoptera: Pteromalidae) is one of the most effective parasitoids associated with soft scale insects in Egypt and was found emerged from W. mimosae (Signoret). Evans and Abd-Rabou (2013) found about seven parasitoids associated with W. mimosae.…”
Section: C) Effect Of Mean Relative Humiditymentioning
confidence: 99%
“…Ben-Dov and Guerrieri (2009) recorded the parasitoid Anicetus africanus (Girault) (Hymenoptera, Encyrtidae) newly recorded from Israel associated with W. mimosae. Badary and Abd-Rabou (2011) mentioned that the pteromalid parasitoid, Scutellista caerulea (Fonscolombe) (Hymenoptera: Pteromalidae) is one of the most effective parasitoids associated with soft scale insects in Egypt and was found emerged from W. mimosae (Signoret). Evans and Abd-Rabou (2013) found about seven parasitoids associated with W. mimosae.…”
Section: C) Effect Of Mean Relative Humiditymentioning
confidence: 99%
“…Unlike the other major parasitoids of P. nigra , the parasitoid Scutellista caerulea Fonscolombe (Hymenoptera: Pteromalidae) can provide an effective control for P. nigra in high-temperature environments. Scutellista caerulea Fonscolombe is an egg parasitoid of multiple species of scale insects, including Ceroplastes rusci Linnaeus, Saissetia oleae Olivier, Coccus hesperidum Linnaeus, and Ceroplastes floridensis Comstock [ 26 , 27 , 28 ]. Larvae of S. caerulea are ectoparasitic and feed on host eggs under its abdomen [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted by Awamelah et al (2009) in Jordan found that the S. caerulea was highly abundant from September to October, and that its population density significantly decreased from November to December [ 30 ]. Badary and Abd-Rabou (2011) investigated the parasitism rate of S. caerulea at eight locations in Egypt and found that its parasitism rates were highest from September to October [ 28 ]. Additionally, S. caerulea was recently found in parasitized P. nigra collected in a rubber tree nursery in Hainan, China, with more than 60% of parasitism rate in the field [ 31 ].…”
Section: Introductionmentioning
confidence: 99%